Deterministic Multi-Item Inventory Systems with Limited Capacity - Zoller, Klaus (Management Science, 1977)
Available storage space frequently limits the aggregate stock level carried in multi-item inventory systems. In the deterministic case, the economic impact of storage capacity constraints may be reduced, and the utilization of the available facilities increased, by replenishment policies which include delivery schedules designed to avoid unnecessary clustering of order arrivals in the course of time. Under the assumption of a pure cycle reordering mode, simple expressions are derived for minimum storage space requirements and the associated optimal delivery schedules.